Brethren of the net : American entomology, 1840-1880 - Sorensen, Willis Conner (History of American science and technology series., 1995)
Sorensen asks how it came about that, within the span of forty years, the American entomological community developed from a few gentlemen naturalists with primary links to Europe to a thriving scientific community exercising world leadership in entomological science. He investigates the relationship between American and European entomology, the background of American entomologists, the implications of entomological theory, and the specific links between 19th-century American society and the rapid institutional growth and advances in theoretical and applied entomology. This book illuminates an important period in entomological research and describes the careers and scientific concerns of hundreds of little-known American men and women. With implications for the history of entomology, the history of science, and American social and intellectual history, this study invites comparisons with other professional scientific groups, such as the geologists and botanists. Sorensen suggests that Americans contributed more directly to evolutionary theory than has been recognized. He also suggests that a decentralized, federal political structure in the United States provided a more congenial environment for natural history investigations than did the centralized structures of European states. Based primarily on the correspondence of American entomologists, Brethren of the Net draws together information from diverse sources to illuminate an important chapter in the history of American science.